Sprouting buds in vitro teak (Tectona grandis L. f.) - Rojas-Parajeles, Fabiana (2012)
Teak (Tectona grandis L. f.) is an exotic timber species introduced to Costa Rica for commercial plantations due to the high demand for its wood, rapid growth and high-quality. Initially the seed was use as the only planting material, but the poor quality of many of the plantations resulted in the initiation of genetic improvement programs. The introduction of clonal propagation in these programs and the establishment of in vitro culture techniques became import tools for mass propagation of the selected elite trees. On the foregoing, this work focused on assessing the effect of several concentrations of two growth regulators, benzylaminopurine (BA) and indole acetic acid (AIB), alone and in combination, in the budding of dormantes buds and callus formation of teak. Both the statistical analysis and the visual observation showed that the treatment consisted of 0.005 mg/l of IAA was the best to increase the budding of the dormant buds and to decrease the callus formation.